Os professores de ciências e suas práticas: uma proposta didática para o ensino do conteúdo estações do ano - Jesus, Daniel Marcos de (2016)
In this work, we analyze the understanding of Science, Geography and Education´s teachers of São Miguel das Matas, Bahia, about teaching and learning process of Seasons content that has been reflected on the construction and using of a didactic material (model System Earth-Sun), developed from a workshop with teachers who teach science´s classes in elementary school. The methodology has been based in questionnaires, videos and experimental demonstrations. The results showed that many science´s teachers have difficulties regarding to the understanding of the Seasons content. As a result, we can say that a didactic workshop in Seasons concept could make better the understanding of this content.